Nutrient recovery from effluent of anaerobic digester treating swine wastewater via struvite precipitation: A case study in Hue City, Vietnam - Ho Thi Xuan, Tuy; Te Minh, Son; Khac Lieu, Pham (Hue University Journal of Science: Natural Science, 2025)
Recently, the recovery of nutrients from nutrient-rich wastewater has attracted considerable attention as a sustainable alternative to contaminant removal. This study investigated the recovery of nitrogen (N) and phosphorus (P) from the effluent of an anaerobic digester treating swine wastewater in Hue City, Vietnam, through struvite precipitation. The effects of pH, reaction time, and NH4+/Mg2+/PO43– (AMP) molar ratio on nutrient recovery efficiency and struvite formation were evaluated by using a Jar-Test system. The results reveal that increasing pH adversely affected N recovery because of NH3 volatilisation, whereas P recovery and struvite formation improved slightly. The best struvite formation was observed at pH 9.0, the reaction time of 30 min, and the AMP molar ratio of 1:1.5:1.5 with a recovery efficiency above 90% and the N and P removal efficiencies of 70% and 57.1%, respectively. X-ray diffraction analysis confirmed that struvite was the primary crystalline product. Additionally, the struvite precipitate contained 4.6% N, 12.5% P, and 11.4% Mg under the most appropriate conditions. This study demonstrates that struvite precipitation efficiently recovered nutrients from anaerobic digestion effluents.